Aflatoxin M1 Concentration in Various Dairy Products: Evidence for Biologically Reduced Amount of AFM1 in Yoghurt. - Amir Rahimirad; Hassan Maalekinejad; Araz Ostadi; Samal Yeganeh; Samira Fahimi (Tehran University of Medical Sciences, 2014)
Aflatoxin M1 (AFM1), a carcinogenic substance is found in milk and dairy products. The effect of season and type of dairy products on AFMi level in northern Iran was investigated in this study.Three hundred samples (each season 75 samples) including raw and pasteurized milk, yoghurt, cheese, and cream samples were collected from three distinct milk producing farms. The samples were subjected to chemical and solid phase extractions and were analyzed by using HPLC technique. Recovery percentages, limit of detection and limit of quantification values were determined.Seventy percent and 98% were the minimum and maximum recoveries for cheese and raw milk, respectively and 0.021 and 0.063 ppb were the limit of detection and limit of quantification values for AFM1. We found that in autumn and winter the highest level (0.121 ppb) of AFM1 in cheese and cream samples and failed to detect any AFM1 in spring samples. Interestingly, our data showed that the yoghurt samples had the lowest level of AFM1 in all seasons.There are significant differences between the AFM1 levels in dairy products in various seasons and also various types of products, suggesting spring and summer yoghurt samples as the safest products from AFM1 level point of view.